Unraveling the generalized Bergshoeff-de Roo identification - Achilleas Gitsis; Falk Hassler (Journal of High Energy Physics)
Abstract We revisit duality-covariant higher-derivative corrections which arise from the generalized Bergshoeff-de Roo (gBdR) identification, a prescription that gives rise to a two parameter family of α ′ -corrections to the low-energy effective action of the bosonic and the heterotic string. Although it is able to reproduce all corrections at the leading and sub-leading (α ′2) order purely from symmetry considerations, a geometric interpretation, like for the two-derivative action and its gauge transformation is lacking. To address this issue and to pave the way for the future exploration of higher-derivative (=higher-loop for the β-functions of the underlying σ-model) corrections to generalized dualities, consistent truncations and integrable σ-models, we recover the gBdR identification’s results from the Poláček-Siegel construction that provides a natural notion of torsion and curvature in generalized geometry.